Large hollow porous quartz glass base material and hollow synthetic quartz glass cylinder

By controlling the rotational circumferential speed and frequency coefficient γ of the soot body, the problems of uneven density distribution and cracks during the growth of large soot bodies at low speeds are solved, and stable growth and homogenization of finished quartz glass cylinders are achieved.

CN119461788APending Publication Date: 2025-02-18SHIN ETABU QUARTZ PRODS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411625772.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-07-15
Filing Date
2021-07-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When manufacturing large hollow porous quartz glass base material (smoke body), there is a problem that the operation of extracting the target from the soot body becomes difficult, especially in the case of large weight and large diameter, which leads to the growth process. Generate centrifugal forces, vibrations and local defects.

Method used

By controlling the rotational circumferential speed of the smoke body to remain fixed, and setting the frequency coefficient γ within the range of 0.13≤γ<1.0 during growth, the reciprocating speed and rotation speed of the burner are adjusted to avoid uneven density distribution and cracks. The emergence of

Benefits of technology

The stable growth of large soot bodies under low rotation speed conditions is achieved, avoiding the problem of uneven cracks and density distribution, and simplifying the target extraction process. The resulting quartz glass cylinder has uniform chlorine and OH concentration distribution, optical and Hot thermal properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461788A_ABST
    Figure CN119461788A_ABST
Patent Text Reader

Abstract

Provided are a large hollow porous quartz glass base material and a hollow synthetic quartz glass tube, which are capable of producing a soot body even for a soot body having an outer diameter exceeding 300 mm without significantly increasing the load on a device, such as centrifugal force generated during growth, and which do not crack or break the soot body even when produced at low-speed rotation. And the target is easy to pull out. The present invention relates to a method for manufacturing a hollow porous quartz glass base material by an OVD method, in which the rotational speed of a soot body that fluctuates during growth is varied on the basis of the outer diameter of the soot body, thereby controlling the rotational circumferential speed of the soot body to be substantially constant, and in a range in which the outer diameter of the soot body exceeds 250 mm, [gamma] = S / (L.Nm) [S is the moving speed of a burner (mm / min), and [L.Nm is the moving speed of the burner (mm / min)], and [L.Nm is the moving speed of the burner (mm / min)]. L is the movement distance (mm) of the combustor, and Nm is the minimum value (rpm) of the rotating speed of the fluctuation of the soot body. The frequency coefficient gamma is set to be in the range of 0.13 < = gamma < 1.0.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese invention patent application filed on July 6, 2021, with application number 202110764980.2, and invention name “Large hollow porous quartz glass base material and its manufacturing method”. Technical Field

[0002] The present invention relates to a large hollow porous quartz glass base material and a method for producing the same, and a hollow synthetic quartz glass tube using the same and a method for producing the same, and in particular, to a large hollow porous quartz glass base material having an outer diameter exceeding 300 mm and a method for producing the hollow porous quartz glass base material capable of appropriately producing the large hollow porous quartz glass base material, and a hollow synthetic quartz glass tube using the same and a method for producing the same. Background Art

[0003] Synthetic quartz glass is widely used in the optical, semiconductor, and chemical industries, especially as a lens material for projection and exposure systems in microlithography, as a jig for semiconductor manufacturing, and as a material for optical fibers.

[0004] The manufacture of hollow synthetic quartz glass cylinders is generally to manufacture a hollow porous synthetic quartz glass base material (soot body) and sinter it to make it transparent. In the manufacture of soot bodies, the OVD method (Outside Vapor Deposition) is known, which converts silicon-containing raw materials into fine SiO2 particles by flame hydrolysis or thermal decomposition and deposits them on the outer surface of a target rotating around its long axis, thereby manufacturing a soot body.

[0005] The hollow porous quartz glass matrix (soot body) requires an operation to extract the target before sintering, and the extraction operation causes the target and the hollow soot body to rotate relative to each other or move in the long axis direction. This operation is extremely difficult when the soot body and the target are fixed. Furthermore, even if it can be extracted by applying a large force, scratches will be generated on the inner surface of the soot body at this time, and the generated scratches will also become residual defective parts as local defects in the quartz tube after sintering.

[0006] In recent years, the demand for larger quartz tubes has increased due to the increase in the diameter of semiconductor wafers and the size of optical fiber base materials. In order to manufacture large quartz tubes, the hollow porous quartz glass base material (soot body) as an intermediate body in the manufacture also needs to be larger and heavier. However, due to the large weight and large diameter of the soot body, there is a problem that it becomes difficult to extract the target from the soot body. It is difficult to achieve the following two things: during the growth of the soot body, the target and the soot body become one and follow the target, the soot body rotates, and the target can be extracted from the soot body after the soot growth.

[0007] In addition, in the OVD method, a plurality of burners for synthesizing glass particles are arranged at fixed intervals, and the rows of burners are relatively reciprocated (swinged) in the rotating starting member (target), and the glass particles are deposited in layers on the target, so that a soot body can be obtained. At the turning point of the swing, the swing speed instantly becomes zero, so the actual time of being irradiated with the flame is longer than that of the part swinging at a steady speed. Therefore, the amount of glass particles deposited at the turning point is large, and unevenness is generated in the long axis direction. Therefore, in Patent Document 1, a traverse method is described in which a soot body with a uniform outer diameter in the long axis direction is obtained by moving the swinging turning position a specified distance each time in order to disperse the deposition in the long axis direction. As a method for dispersing the deposition amount and density distribution, such a traverse method is known.

[0008] Furthermore, in the OVD method, since the soot body is deposited on the outer surface of the target while rotating around the long axis, if the rotation speed of the soot body is fixed, the circumferential speed of the outer surface of the soot body becomes faster as the outer diameter of the soot body grows, and the irradiation time per unit area becomes shorter, so that a radially uniform soot body cannot be obtained. In recent years, in order to improve productivity and reduce costs, the development of large-diameter and thick-walled soot bodies, especially large-diameter soot bodies with an outer diameter exceeding 300 mm, has a significant impact, and it is necessary to reduce the rotation speed as the outer diameter of the soot body grows to keep the circumferential speed constant. Furthermore, even if the circumferential speed is fixed, when the speed is faster than a certain speed, when the outer diameter increases in the later stage of growth, vibration occurs due to a slight eccentricity of the radial center of gravity, or the load on the rotating device increases accordingly, and stable manufacturing cannot be performed. Furthermore, when the circumferential speed is higher than a certain speed, the soot body does not follow the rotation of the target, and idles at the interface between the soot body and the target, so that the soot body cannot stably rotate at a fixed speed. This problem can be avoided by firmly fixing the soot body to the target, but in this case, the aforementioned target extraction operation becomes extremely difficult, and even if the target can be extracted, local defects will occur. Therefore, the circumferential speed constant condition at a low rotation speed is indispensable.

[0009] However, when the rotation condition is set to a low level in order to increase the size and keep the peripheral speed constant, cracks or breakages often occur during or after the growth. Furthermore, even if it does not reach this level, when the treatment with a chlorinating agent is performed, the chlorine concentration distribution of the synthetic quartz glass tube after sintering becomes uneven, and when the treatment with a chlorinating agent is not performed, the OH group concentration distribution becomes uneven, so it is impossible to obtain a quartz glass tube with optically homogeneous physical properties.

[0010] In the manufacture of optical fibers, the difference in chlorine concentration between the radial and circumferential directions is important. In particular, it has become clear from recent studies that fiber curling is improved by reducing the difference in chlorine concentration distribution in the circumferential direction. When drawing a large-diameter preform, the amount of drawing per unit length becomes longer, and the deformation time in the drawing furnace becomes longer, so the local homogeneity of the cladding part affects the properties of the fiber. Therefore, if the size of the glass matrix for the cladding becomes larger, the stability of the chlorine concentration in a smaller range becomes important.

[0011] Quartz glass cylinders manufactured without chlorination treatment are mostly used as materials for quartz glass fixtures and lamp materials used in semiconductor manufacturing equipment. In order to obtain such quartz glass materials, they are molded and heat-processed into the desired size. However, if the OH group concentration difference is large at this time, viscosity distribution will occur in the cylinder, resulting in unstable shapes such as uneven thickness, biased to one side, and elliptical. This is also the same as the aforementioned optical fiber. If the glass size becomes larger, it will appear more significantly. Therefore, the stability of the OH group concentration in a small range becomes important.

[0012] Regarding the reciprocating motion of the burner and the rotation of the support body in the OVD method, Patent Document 2 records the following: the surface base temperature is maintained between 1050°C and 1350°C, the average circumferential speed is maintained at 8m / min to 15m / min, and the parallel speed (swing speed) of the burner row is maintained between 300mm / min to 800mm / min, thereby enabling the manufacture of a base material with almost no local axial density variation. However, in the method described in Patent Document 2, for example, when the swing distance is set to 100mm, the swing speed is set to 800mm / min, and the average circumferential speed is set to 9m / min, if the outer diameter of the deposited body (hereinafter, the outer diameter is also represented as OD) is grown from 100mm to 300mm, the rotation speed needs to be set from 19.1rpm to 6.4rpm. However, when manufacturing is carried out under this condition, cracks enter during growth and growth cannot continue.

[0013] In addition, Patent Document 3 records: In a method of moving the turning position of a reciprocating motion in a fixed direction at a predetermined distance each time and moving the turning position in the opposite direction at a predetermined position, the shape change (axial convexity and concavity of the soot) is suppressed by setting the rotation speed to a fixed value and setting the conditions to have the following relationship.

[0014] A=(r / v)×L shows the value of 40≥A≥8

[0015] [r = rotation speed (rpm), v = reciprocating speed (mm / min), L = burner spacing]

[0016] In the method described in Patent Document 3, for example, when the swing speed is 850 mm / min and the swing width is 100 mm, in order to make A within the specified range, the rotation speed r (rpm) needs to be 68≤r≤320. However, when the outer shape of the deposited body is large, for example, OD300 mm, the surface circumferential speed p (m / min) is as fast as 64≤p≤301, generating a strong centrifugal force. The greater the weight and the larger the diameter, the greater the force, so vibration will occur, or a rigid device and target that can withstand the centrifugal force will need to be made, which becomes expensive, and further, there is a problem of cracks during growth. Furthermore, Patent Document 3 is a method for manufacturing a solid optical fiber preform by depositing silica glass particles on the surface of a starting rod, and is not a method for manufacturing a hollow porous silica glass base material. In the method described in Patent Document 3, in order to manufacture a soot body with an outer diameter of more than 300 mm without idling between the interface with the target, it is necessary to firmly fix the target and the soot body, but in such a case, there is also a problem that it is difficult to extract the target.

[0017] In addition, Patent Document 4 records the following: By setting the reciprocating speed (swinging speed) and the rotation speed, when the starting rod and the burner reciprocate (swing) once and return to the original position, the rotation position of the starting rod is offset from the original position by half a cycle, thereby suppressing the change in the diameter in the longitudinal direction, and the following conditions are recorded.

[0018] (L / V)×N (rpm)=n+0.5±0.1

[0019] [L = moving distance (mm), V = reciprocating speed (mm / min), N = rod speed (rpm), n: any integer]

[0020] In the method described in Patent Document 4, when reciprocating once, the rotation position is offset by 0.5 rotation cycles (180°), so when reciprocating twice, the rotation position is offset by 1 circle (360°). For example, when the swing speed is 850 mm / min and the swing width is 100 mm, the above formula (100 mm / 850 mm / min×12.75 rpm=1.5) is satisfied when the rotation speed is 12.75 rpm. However, in the case of 12.75 rpm, the return position of the swing once every 3 circles is consistent with the timing of 1 rotation, and a density distribution is formed in the soot body in both the long axis direction and the radial direction. Furthermore, Patent Document 4 is also a method for depositing glass particles on the surface of the starting rod to produce a solid glass particle deposition body, and it is not a method for producing a hollow porous quartz glass base material.

[0021] As described above, all patent documents show the local density distribution of the soot body under low rotation speed conditions that enables extraction of targets from a soot body having an outer diameter exceeding 300 mm, but do not provide an invention for suppressing the occurrence of cracks by solving this distribution.

[0022] Prior Art Literature

[0023] Patent Literature

[0024] Patent Document 1: Japanese Patent Application Laid-Open No. 3-228845

[0025] Patent Document 2: Japanese Patent Application No. 2001-504426

[0026] Patent Document 3: Japanese Patent Application Publication No. 2002-167228

[0027] Patent Document 4: Japanese Patent Application Publication No. 2013-43810 Summary of the invention

[0028] Problems to be solved by the invention

[0029] The present invention aims to provide a large-sized hollow synthetic quartz glass porous base material and a method for producing the same, and a hollow synthetic quartz glass cylinder and a method for producing the same, which can produce a soot body without significantly increasing the load on a device such as the centrifugal force generated during growth, even if the soot body has an outer diameter exceeding 300 mm, and further eliminate the local density distribution of the soot body under the condition of a certain low rotation speed of the circumferential speed accompanying the enlargement of the soot body having an outer diameter exceeding 300 mm, and even when producing by low-speed rotation, cracks and breakages are not generated in the soot body, and the target can be easily extracted from the enlarged soot body.

[0030] Means for solving problems

[0031] In order to solve the above problem, the soot body was investigated and it was found that not only the amount of deposition but also the density of the deposited layer differed at the turning point of the reciprocating movement of the burner in the soot body. In the present invention, the reciprocating movement of the burner is called swinging. Figure 4 This is a graph showing the return position of the reciprocating movement (swing) of the burner and the density distribution of the deposited layer in the long axis direction of the soot body. Figure 4 As shown, at the turn-back position of the burner, the swing speed becomes higher density than when it moves at a steady speed, and this is repeated and deposited to generate an axial density distribution in the soot body.

[0032] Further investigation revealed that a strong density difference was locally formed not only in the axial direction but also in the radial direction. A detailed analysis of the local density variation in the radial direction revealed that the turning point of the oscillation coincided with the timing of one rotation. Figure 5 is a graph showing the density distribution of the soot body in the radial direction. Figure 5 As shown, it can be seen that under normal circumstances, the swing return positions where the density becomes high are dispersed along the circumferential direction, but when the swing return and the timing of one circle are consistent and grown for more than a certain period of time, the high-density domain is not dispersed, and the high-density area overlaps with the low-density area in the circumferential direction, and there is a part where the density becomes extremely low. Figure 5 Here, γ is the frequency coefficient calculated by the following formula (1).

[0033] γ = S / (L·N m )···(1)

[0034] [In the above formula (1), S is the moving speed of the burner (mm / min), L is the moving distance of the burner (mm), N m It is the minimum value (rpm) of the rotation speed of the soot body.]

[0035] That is, it was found that not only the deposition amount and density distribution in the axial direction but also the local density distribution in the radial direction were generated in the soot body, and various problems such as cracks, chlorine concentration distribution and OH group concentration distribution were generated due to the influence of these. It was further found that by controlling the rotation circumferential speed of the soot body during growth to be substantially constant and setting the frequency coefficient γ to a specified range, even if the soot body has an outer diameter exceeding 300 mm, the soot body can be produced without significantly increasing the load on the device such as the centrifugal force generated during growth, and the generation of cracks can be suppressed, and the unevenness of the chlorine concentration and the OH group concentration can be suppressed. It was further found that by setting it to the above setting, the target can be easily extracted from the soot body with a large diameter.

[0036] That is, the method for producing a hollow porous quartz glass base material of the present invention is a method for producing a hollow porous quartz glass base material, comprising the steps of: arranging a plurality of glass fine particle synthesis burners at predetermined intervals, reciprocating the burners to deposit glass fine particles on a rotating target to grow a soot body; and extracting the target from the soot body to produce the hollow porous quartz glass base material, wherein the rotation speed of the soot body is changed based on the outer diameter of the soot body that changes during growth, thereby controlling the rotation circumferential speed of the soot body to be substantially constant, and setting the frequency coefficient γ calculated by the following formula (1) to the range of the following formula (2) in the range where the outer diameter of the soot body exceeds 250 mm.

[0037] γ = S / (L·N m )···(1)

[0038] 0.13≤γ<1.0···(2)

[0039] [In the above formula (1), S is the moving speed of the burner (mm / min), L is the moving distance of the burner (mm), N m is the minimum value (rpm) of the rotational speed of the soot body.]

[0040] Preferably, when the folding position in the reciprocating movement of the burner is moved a predetermined distance each time under wabbling conditions, when the movement amount of the folding position in one reciprocation of the burner is less than 1 / 3 of the diameter of the flame of the burner irradiated onto the soot body, the range of the above formula (2) is set. In the present invention, moving the folding position in the reciprocating movement of the burner a predetermined distance each time is referred to as wabbling. In the method of the present invention, by wabbling under the above conditions, a hollow porous quartz glass base material with extremely small density variation and uniformity can be obtained. In addition, when the movement amount of the folding position exceeds 1 / 3 of the flame diameter under wabbling conditions, the folding position is dispersed, so the heat is also dispersed, and it is difficult to produce problems such as cracks and uneven physical properties.

[0041] Preferably, the frequency coefficient γ is 0.13 or more and 0.3 or less. By making the frequency coefficient γ 0.3 or less, a hollow synthetic quartz glass tube can be obtained which has no cracks or breaks in the soot body, has uniform distribution of chlorine concentration and distribution of OH group concentration, and is extremely homogeneous in terms of optical and thermal properties.

[0042] The method for producing a synthetic quartz glass tube of the present invention is characterized by using a hollow porous quartz glass base material obtained by the method for producing a hollow porous quartz glass base material of the present invention.

[0043] The first embodiment of the hollow porous silica glass base material of the present invention is a large cylindrical hollow porous silica glass base material having an outer diameter exceeding 300 mm and a length exceeding 2 m, characterized in that the average density of the base material as a whole is 0.55 g / cm 3 The above, and the density variation per unit length at four points equidistant from the inner surface in the radial direction in four directions of every 90° of the cylindrical cross section is less than 10% / cm relative to the average value of the four points, and does not include cracks.

[0044] A second embodiment of the hollow porous silica glass base material of the present invention is a large cylindrical hollow porous silica glass base material having an outer diameter of 500 mm or more and a length of 1.0 m or more, characterized in that the average density of the base material as a whole is 0.55 g / cm 3 The above, and the density variation per unit length at four points equidistant from the inner surface in the radial direction in four directions of every 90° of the cylindrical cross section is less than 10% / cm relative to the average value of the four points, and does not include cracks.

[0045] The large hollow porous silica glass base material can be preferably obtained by the method for producing the hollow porous silica glass base material.

[0046] A third aspect of the hollow porous quartz glass base material of the present invention is a hollow porous quartz glass base material obtained by the method for manufacturing the hollow porous quartz glass base material, characterized in that the material is manufactured under the aforementioned shaking conditions and under the conditions that the amount of movement of the folding position in one reciprocation of the burner is 1 / 3 or less of the diameter of the flame of the burner irradiated onto the soot body, and the density variation per unit length at four points equidistant from the inner surface in the radial direction in four directions of every 90° of the cylindrical cross section is 2% / cm or less relative to the average value of the four points.

[0047] A first aspect of the hollow synthetic quartz glass cylinder of the present invention is characterized in that it is obtained by dehydrating and vitrifying the hollow porous quartz glass base material, has an outer diameter of 200 to 500 mm, a length of 0.7 m to 3.5 m, an OH group concentration of less than 5 ppm, a chlorine content of 500 ppm to 3000 ppm, and does not include an appearance defective portion caused by cracks in the porous member.

[0048] In the first aspect of the hollow synthetic quartz glass tube, it is preferred that the “difference between the maximum value and the minimum value” of the chlorine concentration at four positions every 90° in the circumferential direction which are equidistant from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass tube is within 15% of the average value of the four positions.

[0049] A second embodiment of the hollow synthetic quartz glass tube of the present invention is characterized in that it is obtained by pre-sintering and vitrifying the hollow porous quartz glass base material, has an outer diameter of 200 to 500 mm, a length of 0.7 m to 3.5 m, an OH group concentration of 50 ppm to 500 ppm, and does not include an appearance defective portion caused by cracks in the porous member.

[0050] In the second aspect of the hollow synthetic quartz glass tube, it is preferred that the “difference between the maximum value and the minimum value” of the OH group concentration at four positions every 90° in the circumferential direction which are equidistant from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass tube is within 15% of the average value of the four positions.

[0051] A third aspect of the hollow synthetic quartz glass tube of the present invention is a hollow synthetic quartz glass tube obtained by vitrifying the third aspect of the hollow porous quartz glass base material, characterized in that a “difference between the maximum value and the minimum value” of the chlorine concentration at four positions every 90° in the circumferential direction at equal distances from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass tube is 10% or less with respect to an average value at the four positions.

[0052] A fourth aspect of the hollow synthetic quartz glass tube of the present invention is a hollow synthetic quartz glass tube obtained by vitrifying the third aspect of the hollow porous quartz glass base material, characterized in that a “difference between the maximum value and the minimum value” of the OH group concentration at four positions every 90° in the circumferential direction at equal distances from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass tube is 10% or less with respect to an average value at the four positions.

[0053] Effects of the Invention

[0054] According to the present invention, a large-sized hollow synthetic quartz glass porous base material and a method for producing the same, and a hollow synthetic quartz glass cylinder and a method for producing the same are provided. Even in the case of a soot body having an outer diameter exceeding 300 mm, the soot body can be produced without significantly increasing the load on the device such as the centrifugal force generated during the growth, and the local density distribution of the soot body under the condition of a certain low rotation speed accompanying the enlargement of the circumferential speed of the soot body exceeding 300 mm in outer diameter is eliminated. Even in the case of production by low-speed rotation, cracks and breakages are not generated in the soot body, and the target can be easily extracted from the enlarged soot body.

[0055] Furthermore, according to the present invention, a large hollow synthetic quartz glass cylinder can be obtained which has a uniform chlorine concentration or OH group concentration and extremely homogeneous optical and thermal properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a schematic explanatory diagram showing a method for producing a hollow porous silica glass base material according to the present invention.

[0057] Figure 2 These are schematic explanatory views showing the movement of a burner in the method for producing a hollow porous quartz glass base material of the present invention, wherein (a) shows a non-shaking condition, and (b) shows a shaking condition.

[0058] Figure 3 This is a schematic explanatory diagram showing irradiation with a burner in the method for producing a hollow porous quartz glass base material of the present invention.

[0059] Figure 4 It is a graph showing the turning point of the reciprocating movement of the burner and the density distribution of the deposited layer in the long axis direction of the soot body.

[0060] Figure 5 It is a graph showing the density distribution of the soot body in the radial direction.

[0061] Figure 6 This is a schematic explanatory diagram showing a method for measuring the density in the hollow porous silica glass base material of the present invention.

[0062] Description of Reference Numerals

[0063] 10: manufacturing device, 12: soot body, 14: target, 16: burner group for glass particle synthesis, 16a: burner for glass particle synthesis, 18: swing and up and down movement device of the burner group for glass particle synthesis, 20: target holding rotation mechanism, 22: burner flame, d: flame irradiation diameter, L: swing distance, b: burner interval, α: shaking displacement DETAILED DESCRIPTION

[0064] Hereinafter, embodiments of the present invention will be described, but these embodiments are shown by way of example, and various modifications are possible without departing from the technical concept of the present invention. In the drawings, the same components are denoted by the same reference numerals.

[0065] Figure 1 : is a schematic diagram showing a method for manufacturing a hollow porous quartz glass base material of the present invention. The method for manufacturing a hollow porous quartz glass base material of the present invention is as follows: a plurality of glass particle synthesis burners 16a are arranged, the burners 16a are reciprocated, and the glass particles are deposited on a rotating target 14 to grow a soot body 12, thereby manufacturing a hollow porous quartz glass base material, wherein the rotation speed of the soot body 12 is changed based on the outer diameter of the soot body 12 that changes during growth, thereby controlling the rotation circumferential speed of the soot body 12 to be substantially constant, and the frequency coefficient γ calculated by the following formula (1) in the range where the outer diameter of the soot body exceeds 250 mm is set to the range of the following formula (2). In addition, substantially constant means ±5%.

[0066] γ = S / (L·N m )···(1)

[0067] 0.13≤γ<1.0···(2)

[0068] [In the above formula (1), S is the moving speed of the burner 16a (mm / min), L is the moving distance of the burner 16a (mm), N m is the minimum value (rpm) of the variable rotation speed of the soot body 12.]

[0069] exist Figure 110 is a manufacturing device for manufacturing a hollow porous quartz glass base material, including: a target holding and rotating mechanism 20 for rotating and holding a target 14 and controlling the rotation speed (rpm); a glass particle synthesis burner group 16 in which a plurality of glass particle synthesis burners 16a are arranged at predetermined intervals; and a burner group movement control device 18 for controlling the swing and up and down movement of the burner group 16.

[0070] like Figure 1 As shown, a target holding and rotating mechanism 20 for controlling the rotation speed of a target 14 and a glass particle synthesis burner group 16 whose swinging (reciprocating movement) and up-and-down movement are controlled by a burner group movement control device 18 are used. The rotation speed of the soot body 12 is changed based on the outer diameter of the soot body 12 which changes during growth, thereby controlling the rotational circumferential speed of the soot body 12 to be substantially constant. Under the condition that the frequency coefficient γ calculated by the above formula (1) is set to be greater than 0.13 and less than 1.0, glass particles generated by a hydrolysis reaction of a flame of a glass particle synthesis burner 16a supplied with a glass raw material (such as SiCl4) are deposited on the outer surface of a rod-shaped target 14 which is rotationally held and controlled by the target holding and rotating mechanism 20. After the soot body 12 is grown, the target 14 is pulled out from the soot body 12, thereby making it possible to manufacture the hollow porous quartz glass base material of the present invention.

[0071] The reason for the cracks is the local density difference generated in the soot body, which is caused by the timing of the soot body rotating one circle and the timing of the swing of the burner. Here, consider rotating Y circles during X swings (X / 2 reciprocating). The time required for X swings is X (L / S), and the time required for Y rotations is Y / N. Here, L is the moving distance of the burner (mm), S is the moving speed of the burner (mm / minute), and N is the rotation speed of the soot body (rpm). The timing of the swing and the rotation is consistent, which means that X (L / S) = Y / N, X / Y = S / (LN). This X / Y is called the frequency coefficient γ. Figure 5 The γ shown is the frequency coefficient.

[0072] For example, when rotating 2 times during 2 swings, γ=X / Y=2 / 2=1. In this case, in the 1st turn, the timing of the rotation and swinging coincides on the left end of the swing, and in the next turn, the timing coincides on the right end. Since multiple burners are arranged at equal intervals, if the adjacent burners are also considered, the rotation and swinging coincide in each turn. The area near the coincidence becomes high density, and the area where it is not the case becomes extremely low density. Due to the large density difference, it enters the crack during growth and after growth.

[0073] In the present invention, by controlling the surface circumferential speed of the soot body to be substantially constant and making γ less than 1.0 in the range where the outer diameter of the soot body exceeds 250 mm, a large hollow porous quartz glass matrix without cracks or breakages can be obtained. In the present invention, the surface circumferential speed of the soot body is preferably 5 to 50 m / min, more preferably 5 to 10 m / min.

[0074] Furthermore, based on the same idea, even if the rotation and return are consistent not every time but several times, it is also affected. Table 1 shows the frequency of rotation and swing when swing X=2 and Y turns are even numbers, and Table 2 shows the frequency of rotation and swing when swing X=2 and Y turns are odd numbers.

[0075] [Table 1]

[0076]

[0077] [Table 2]

[0078]

[0079] In the case of γ=2 / 3=0.667, which means three rotations during two swings (one reciprocation), there is a slight difference in density compared to when the turning position of one swing after three rotations coincides with the position of one rotation and coincides with each time. In the case of γ=2 / 4=0.5, which means four rotations during two swings (one reciprocation), the turning position of two swings coincides with the position of one rotation in four rotations, resulting in a density difference. Since there is no density difference of the same degree as when they coincide with each time, it is difficult to cause cracks, but due to the density difference, the distribution of the chlorine concentration and the distribution of the OH group concentration become uneven, and optically homogeneous quartz glass cannot be obtained.

[0080] Therefore, by setting the swing distance, swing speed and rotation speed so that N is the minimum value N under the frequency coefficient γ represented by X / Y=S / (LN) m The value of the frequency coefficient γ at the time becomes γ≤0.3, so that the timing of rotation and oscillation can be set to be inconsistent, and as a result, a quartz glass tube without cracks and with a small chlorine concentration distribution and OH group concentration distribution can be obtained. Since the present invention controls the rotation circumferential speed of the soot body to be substantially constant, the rotation speed of the soot body decreases as the soot body grows. Therefore, in the present invention, by setting the rotation speed N to the minimum value N m It is defined by the frequency coefficient γ when .

[0081] Furthermore, by setting the frequency coefficient γ to 0.13 or more, even when deposition is performed with an outer diameter exceeding 250 mm, it is possible to produce a soot body without causing vibration of the growing soot body or vibration of the apparatus.

[0082] In the present invention, the frequency coefficient γ is 0.13 or more and less than 1.0, and more preferably 0.13 or more and 0.3 or less. By making γ less than 1.0, cracks and fractures of the soot body can be eliminated, and by making γ less than 0.3, a quartz glass tube can be obtained that has no cracks and fractures of the soot body, has uniform distribution of chlorine concentration and distribution of OH group concentration, and is homogeneous in terms of optical and thermophysical properties.

[0083] The method of the present invention may be performed under so-called shaking conditions in which the swung turning position is moved in a fixed direction by a predetermined distance (α) each time and the turning position is moved in the opposite direction at a predetermined position, or may be performed under non-shaking conditions. Figure 2 The following are schematic diagrams showing the movement of the burner in the method for producing a hollow porous quartz glass base material of the present invention, wherein (a) shows the movement under a non-shaking condition and (b) shows the movement under a shaking condition. Figure 2 In the equation, L is the swing distance, b is the burner interval, and α is the shaking displacement. Figure 2 Although the case where the swing distance is the same as the burner interval is shown, in the present invention, the swing distance and the burner interval may be the same or different.

[0084] When the swinging is performed under shaking conditions, when the amount of movement α of the folding position in one reciprocation of the burner is less than 1 / 3 of the diameter of the flame of the burner irradiating the soot body, it is preferably set to the range of the above formula (2). In the method of the present invention, by shaking under the above conditions, a homogeneous hollow porous quartz glass base material with extremely small density variation can be obtained. In addition, when the amount of movement of the folding position under the shaking condition exceeds 1 / 3 of the flame diameter, the folding position is dispersed, so the heat is also dispersed, and it is difficult to cause problems such as cracks and uneven physical properties.

[0085] Figure 3 This is a schematic diagram showing the irradiation of the burner in the method for manufacturing the hollow porous quartz glass base material of the present invention, and d is the flame irradiation diameter. In the case of using shaking, when the amount of movement of the return position in each swing is made less than 1 / 3 of the flame irradiation diameter d expanded from the burner to the deposit body, the overlap between the layers is large, so the method of the present invention is effective. The flame irradiation diameter d can be measured by image analysis of the flame during the growth of the soot body.

[0086] According to the method of the present invention, a large hollow porous quartz glass base material with a small density variation and no cracks or breaks and an outer diameter exceeding 300 mm can be obtained. Specifically, a large cylindrical hollow porous quartz glass base material with an outer diameter exceeding 300 mm and an axial length exceeding 2 m and a large cylindrical hollow porous quartz glass base material with an outer diameter exceeding 500 mm and an axial length exceeding 1.0 m can be obtained. In addition, by the method of the present invention, a large hollow porous quartz glass base material with a weight of more than 100 kg can be obtained. Furthermore, by the method of the present invention, even if the soot body is enlarged in diameter and weight, the target can be pulled out extremely easily.

[0087] The first embodiment of the hollow porous silica glass base material of the present invention is that the average density of the base material as a whole is 0.55 g / cm 3 Large hollow porous quartz glass base material with small density fluctuation, no cracks, outer diameter exceeding 300mm and length exceeding 2m.

[0088] The second embodiment of the hollow porous silica glass base material of the present invention is that the average density of the base material as a whole is 0.55 g / cm 3 A large hollow porous quartz glass base material having a small density variation, no cracks, an outer diameter of 500 mm or more and a length of 1.0 m or more.

[0089] In the first and second aspects of the hollow porous silica glass base material, the average density of the base material as a whole is 0.55 g / cm 3 Above, preferably 0.56 g / cm 3 Above 0.77g / cm 3 Below, more preferably 0.59 g / cm 3 Above 0.68g / cm 3 the following.

[0090] Figure 6 1 is a schematic diagram showing a method for measuring the density variation in the hollow porous silica glass base material of the present invention. Figure 6 As shown, in the four perpendicular lines (A to D) at every 90° of the cylindrical cross section of the hollow porous silica glass base material 12 of the present invention, the radial distance (X mm) from the inner surface of four points (a to d) is measured every 1 cm 3 The density of the hollow porous silica glass base material 12 of the present invention is determined by the difference between the maximum value and the minimum value of the density at the four points (a to d). The density variation per unit length of the hollow porous silica glass base material 12 is 10% / cm or less, preferably 5% / cm or less, and more preferably 2% / cm or less relative to the average value of the four points (a to d) in the four directions (A to D).

[0091] A third aspect of the hollow porous quartz glass base material of the present invention is a hollow porous quartz glass base material, wherein the density variation per unit length at four points equidistant from the inner surface in the radial direction in four directions of every 90° of the cylindrical cross section is 2% / cm or less relative to the average value of the four points. In the method for manufacturing the hollow porous quartz glass base material, the hollow porous quartz glass base material is manufactured under shaking conditions in which the movement amount of the return position in one reciprocation of the burner is 1 / 3 or less of the diameter of the flame of the burner irradiated to the soot body, thereby obtaining a homogeneous hollow porous quartz glass base material with an extremely small density variation of 2% / cm or less.

[0092] The method for manufacturing a synthetic quartz glass tube of the present invention uses a hollow porous quartz glass base material obtained by the method of the present invention. As the method for manufacturing the synthetic quartz glass tube, the hollow porous quartz glass base material can be used to manufacture a synthetic quartz glass tube by a known method without any particular limitation, but preferably, a method of obtaining a synthetic quartz glass tube by dehydration treatment and sintering and vitrification; a method of obtaining a synthetic quartz glass tube by pre-sintering and vitrification. According to the method of the present invention, a large synthetic quartz glass tube with an outer diameter of 200 mm or more can be appropriately obtained without including an appearance defective portion caused by cracks in a porous member, and without cracks or breakages.

[0093] As the large synthetic quartz glass cylinder, specifically, by using a cylindrical large hollow porous quartz glass base material with an outer diameter exceeding 300 mm, a hollow synthetic quartz glass cylinder with an outer diameter of 200 mm or more can be obtained, and by using a cylindrical large hollow porous quartz glass base material with an outer diameter of 500 mm or more, a hollow synthetic quartz glass cylinder with an outer diameter of 300 mm or more can be obtained. In particular, a hollow synthetic quartz glass cylinder with an outer diameter of 200 mm or more and less than 300 mm and an axial length of 2.3 mm or more, and a hollow synthetic quartz glass cylinder with an outer diameter of 300 mm or more and an axial length of 0.7 mm or more are more preferred.

[0094] In the present invention, by using a hollow porous quartz glass base material obtained under the condition that the γ is set to less than 1.0 in the range where the outer diameter of the soot body exceeds 250 mm, a large quartz glass tube can be easily obtained that does not contain an appearance defective portion caused by cracks in the porous member and has no cracks or breaks. This quartz glass tube is particularly suitable as a material for a semiconductor manufacturing jig that is expected to be large. Furthermore, by using a hollow porous quartz glass base material obtained under the condition that the γ is set to less than 0.3, a quartz glass tube can be easily obtained that has no cracks or breaks, has a uniform distribution of chlorine concentration and OH group concentration, and is extremely homogeneous in terms of optical and thermal properties.

[0095] A first embodiment of the hollow synthetic quartz glass tube of the present invention is a hollow synthetic quartz glass tube having an outer diameter of 200 to 500 mm and a length of 0.7 m to 3.5 m obtained by dehydrating and vitrifying the large hollow porous quartz glass base material by chlorine treatment, characterized in that the OH group concentration is less than 5 ppm, the chlorine content is 500 ppm to 3000 ppm, preferably 1000 ppm to 2500 ppm, and does not contain an appearance defective portion caused by cracks in the porous member.

[0096] In the first embodiment of the hollow synthetic quartz glass tube, the "difference between the maximum value and the minimum value" of the chlorine concentration at four positions every 90° in the circumferential direction at equal distances from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass tube is preferably within 15% with respect to the average value of the four positions, and more preferably within 10%.

[0097] A second embodiment of the synthetic quartz glass tube of the present invention is a hollow synthetic quartz glass tube having an outer diameter of 200 to 500 mm and a length of 0.7 m to 3.5 m, obtained by pre-sintering and vitrifying the large hollow porous quartz glass base material without chlorine treatment, characterized in that the OH group concentration is 50 ppm to 500 ppm, preferably 100 ppm to 300 ppm, and does not contain an appearance defective portion caused by cracks in the porous member.

[0098] In the second embodiment of the hollow synthetic quartz glass tube, the "difference between the maximum value and the minimum value" of the OH group concentration at four positions every 90° in the circumferential direction at equal distances from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass tube is preferably within 15% with respect to the average value of the four positions, and more preferably within 10%.

[0099] The third aspect of the synthetic quartz glass cylinder of the present invention is a hollow synthetic quartz glass cylinder obtained by vitrifying the third aspect of the hollow porous quartz glass base material, characterized in that the "difference between the maximum value and the minimum value" of the chlorine concentration at four positions of 90° in the circumferential direction at equal distances from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass cylinder is 10% or less relative to the average value of the four positions. The OH group concentration of the synthetic quartz glass cylinder is preferably less than 5 ppm, and more preferably substantially free of OH groups. In addition, "substantially free of OH groups" means that the content of OH groups in the synthetic quartz glass cylinder is 0 ppm or more and less than 1 ppm.

[0100] The method for vitrifying the hollow porous quartz glass base material is not particularly limited, and a known method can be used, but a method of obtaining a synthetic quartz glass tube by performing a dehydration treatment and sintering and vitrification is preferred, and a method of obtaining a synthetic quartz glass tube by performing a dehydration treatment in a chlorine atmosphere and then sintering and vitrification is more preferred.

[0101] A fourth aspect of the synthetic quartz glass tube of the present invention is a hollow synthetic quartz glass tube obtained by vitrifying the third aspect of the hollow porous quartz glass base material, characterized in that the "difference between the maximum value and the minimum value" of the OH group concentration at four positions of 90° in the circumferential direction at equal distances from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass tube is 10% or less relative to the average value of the four positions. The synthetic quartz glass tube preferably contains substantially no chlorine. In addition, "substantially no chlorine" means that the chlorine content in the synthetic quartz glass tube is 0 ppm or more and less than 20 ppm.

[0102] The method for vitrifying the hollow porous quartz glass base material is not particularly limited, and a known method can be used, but a method of obtaining a synthetic quartz glass tube by dehydration treatment and sintering and vitrification is preferred; a method of obtaining a synthetic quartz glass tube by pre-sintering and vitrification is preferred, and a method of obtaining a synthetic quartz glass tube by dehydration treatment by heating without chlorine treatment and then sintering and vitrification is more preferred.

[0103] Conventionally, when a low rotation condition is set in order to increase the size and keep the circumferential speed constant during the growth of the soot body, when a dehydration treatment is performed in a chlorine atmosphere during the manufacture of the synthetic quartz glass tube, the chlorine concentration distribution in the circumferential direction of the synthetic quartz glass tube becomes non-uniform, and when dehydration is performed by heating without a chlorine treatment, there is a problem that the OH group concentration distribution in the circumferential direction of the synthetic quartz glass tube becomes non-uniform. However, in the method of the present invention, by using a hollow porous quartz glass base material obtained under the condition that the γ is set to 0.3 or less, the chlorine concentration distribution is small even when the dehydration treatment is performed in a chlorine atmosphere, and even when dehydration is performed by heating without a chlorine treatment, an extremely homogeneous synthetic quartz glass tube with a small difference in the OH group concentration distribution can be obtained.

[0104] Such extremely homogeneous synthetic quartz glass cylinders are particularly suitable as materials for optics, optical fibers, and quartz glass jigs and lamps used in semiconductor manufacturing equipment. In particular, it was found that if the difference between the maximum and minimum values ​​of the chlorine concentration distribution at each point in the four directions of the circumferential direction inside the cylinder cross section is within 15% relative to the average value of the four points, the characteristics of the optical fiber, including fiber curling, are not affected.

[0105] In the chlorine concentration distribution of the synthetic quartz glass cylinder dehydrated and sintered to be transparent in a chlorine atmosphere, the difference between the high concentration and the low concentration in four directions of the cylinder circumference is preferably 300 ppm or less, more preferably 200 ppm or less.

[0106] In the OH group concentration distribution of the synthetic quartz glass cylinder dehydrated by heating without chlorine treatment, the difference between the high and low OH group concentrations in four directions of the cylinder circumference is preferably 50 ppm or less, more preferably 25 ppm or less.

[0107] [Example]

[0108] (Example 1)

[0109] A plurality of burners for synthesizing glass particles are arranged at fixed intervals, and the burner array is reciprocated (swung) relative to a rotating target [a ceramic tube with an outer diameter (OD) of 50 mm], and glass particles are deposited in layers on the target to produce a glass particle deposit body. In the so-called OVD method, a soot body is produced under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 140 mm / min (fixed), and a surface peripheral speed of 11 m / min (fixed). The target is pulled out from the soot body to obtain a hollow porous quartz glass base material. The production conditions are shown in Table 3, the results of the obtained hollow porous quartz glass base materials are shown in Table 4, and the measurement results of the synthetic quartz glass tube are shown in Tables 5 and 6.

[0110] [Table 3]

[0111]

[0112] When the soot body is grown from a target OD of 50 mm to an outer diameter (OD) of 400 mm, the rotation speed is reduced from 70.1 rpm to 8.8 rpm under the above conditions. m is 8.8rpm, γ=S / (L·N m )=0.16.

[0113] As a result, although there was slight vibration during the growth of the device, it was able to grow without any problems, and there were no cracks in the soot body. A large hollow porous quartz glass base material (soot body) with an outer diameter of 400 mm, a total axial length of 3500 mm, and a weight of 247 kg was manufactured.

[0114] The average density of the entire soot body and the density variation are measured. Figure 6 The density per unit length at the four points (a to d) at X = 105 mm is calculated, the difference between the maximum and minimum values ​​of the density at the four points (a to d) is defined as the density variation, and the ratio to the average value of the four points is calculated.

[0115] [Table 4]

[0116]

[0117] The average density of the soot body is 0.57g / cm 3 The density variation per unit length at four points at a distance of 105 mm from the inner surface in four directions was 4.4% / cm relative to the average value of the four points, and a hollow porous quartz glass base material with extremely small density variation was obtained.

[0118] The obtained hollow porous quartz glass base material was dehydrated and sintered in a chlorine atmosphere to obtain a synthetic quartz glass tube with an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member and had a good appearance.

[0119] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. The chlorine concentration was measured in four directions by fluorescent X-ray analysis. As an analytical device for measuring the chlorine concentration, a fluorescent X-ray analyzer SPECTRO MIDEX manufactured by SPECTRO was used (the detection limit of the device: chlorine concentration 20ppm). The OH group concentration (OH group) was measured by FT-IR analysis. As an analytical device for measuring the OH group concentration, a Fourier transform infrared spectrometer Nicoletis10 FT-IR manufactured by Thermo Fisher Scientific was used (the detection limit of the device: OH group concentration 1ppm). Regarding the change in chlorine concentration, the difference between the maximum and minimum values ​​of the chlorine concentration at four positions 50mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio relative to the average value of the four points was calculated. The results are shown in Table 5.

[0120] [Table 5]

[0121]

[0122] The chlorine concentration in the four directions of the cylinder was measured, and the result was that the chlorine concentration was 1540-1720ppm. The maximum difference in the four directions was as small as 180ppm, and the variation relative to the average value of the four directions was a homogeneous variation of 10.9%. In addition, the OH group concentration (OH group) was less than 1ppm.

[0123] Furthermore, the soot body produced under the same conditions was heated to dehydrate without chlorine treatment, and then sintered and transparentized to obtain a synthetic quartz glass tube with an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member, and had a good appearance.

[0124] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. The variation of the OH group concentration was measured by measuring the difference between the maximum and minimum values ​​of the OH group concentration at four locations 50 mm from the inner surface of the cylinder cross section at every 90° in the circumferential direction, and calculating the ratio to the average value of the four points. The results are shown in Table 6.

[0125] [Table 6]

[0126]

[0127] The OH group concentration in the four directions around the cylinder was measured and found to be 230-255 ppm. The maximum difference between the four directions was 25 ppm, and the variation relative to the average value in the four directions was uniformly 10.2%. In addition, the chlorine concentration was less than 20 ppm.

[0128] (Example 2)

[0129] A hollow porous quartz glass base material was obtained by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, a soot body was produced under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 200 mm / min (fixed), and a surface peripheral speed of 9 m / min (fixed), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4, and the measurement results of the synthetic quartz glass cylinder are shown in Tables 5 and 6.

[0130] When growing from a target OD of 50 mm to a soot body OD of 400 mm, the rotation speed is reduced from 57.3 rpm to 7.2 rpm under the above conditions. The minimum rotation speed N at this time is m It is 7.2rpm, γ=0.28.

[0131] As a result, a large hollow porous silica glass base material with an outer diameter of 400 mm, a total length of 3500 mm, and a weight of 247 kg can be produced without vibration during growth of the device or cracks in the soot body.

[0132] The average density of the entire soot body and the density variation are measured. Figure 6 The density per unit length at the four points where X = 105 mm is calculated. The average density of the entire soot body is 0.57 g / cm 3 The density variation per unit length at a position 105 mm from the inner surface in four directions is 3.8% / cm relative to the average value of the four points, and a hollow porous quartz glass base material with extremely small density variation is obtained.

[0133] The obtained hollow porous quartz glass base material was dehydrated and sintered in a chlorine atmosphere to obtain a synthetic quartz glass tube with an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member and had a good appearance.

[0134] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of chlorine concentration, the difference between the maximum and minimum chlorine concentrations at four locations 50 mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0135] The chlorine concentration in the four directions of the cylinder was measured, and the result was that the chlorine concentration was 1740-1960ppm. The maximum difference between the four directions was 220ppm, and the variation relative to the average value of the four directions was a homogeneous variation of 11.7%. In addition, the OH group concentration (OH group) was less than 1ppm.

[0136] Furthermore, the soot body produced under the same conditions was heated to dehydrate without chlorine treatment and then sintered to be transparent, thereby obtaining a synthetic quartz glass tube having an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube had no appearance defective parts caused by cracks in the porous member and had a good appearance.

[0137] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. The variation of the OH group concentration was determined by measuring the difference between the maximum and minimum OH group concentrations at four locations 50 mm from the inner surface of the cylinder cross section at every 90° in the circumferential direction, and calculating the ratio to the average value of the four points.

[0138] The OH concentration in the four directions around the cylinder was measured and found to be 225-255 ppm. The difference between the four directions was as small as 30 ppm, and the variation relative to the average value in the four directions was also uniform at 12.4%. In addition, the chlorine concentration was less than 20 ppm.

[0139] (Example 3)

[0140] A hollow porous quartz glass base material was obtained by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, a soot body was produced under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 600 mm / min (fixed), and a surface peripheral speed of 9 m / min (fixed), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4, and the measurement results of the synthetic quartz glass cylinder are shown in Table 5.

[0141] When growing from a target OD of 50 mm to a soot body OD of 400 mm, the rotation speed is slowed down from 57.3 rpm to 7.2 rpm under the above conditions. m It is 7.2rpm, γ=0.84.

[0142] As a result, a large hollow porous silica glass base material with an outer diameter of 400 mm, a total length of 3500 mm, and a weight of 247 kg can be produced without vibration during growth of the device or cracks in the soot body.

[0143] The average density of the entire soot body and the density variation are measured. Figure 6 The density per unit length at the four points where X = 105 mm is calculated. The average density of the entire soot body is 0.57 g / cm 3 The density variation per unit length at a position 105 mm from the inner surface in four directions is 9.5% / cm relative to the average value of the four points.

[0144] The obtained hollow porous quartz glass base material was dehydrated and sintered in a chlorine atmosphere to obtain a synthetic quartz glass tube with an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member and had a good appearance.

[0145] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change in chlorine concentration, the difference between the maximum and minimum chlorine concentrations at four locations 50 mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio to the average value was calculated.

[0146] The chlorine concentration in four directions around the cylinder was measured, and the chlorine concentration was 1640 to 2330 ppm. The maximum difference between the four directions was 690 ppm, and the variation relative to the average value of the four directions was 34.9%, which was lower in homogeneity than Examples 1 and 2. In addition, the OH group concentration (OH group) was less than 1 ppm.

[0147] Furthermore, the soot body produced under the same conditions was heated to dehydrate without chlorine treatment, and then sintered and transparentized to obtain a synthetic quartz glass tube with an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member, and had a good appearance.

[0148] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the variation of the OH group concentration, the difference between the maximum and minimum OH group concentrations at four locations 50 mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio to the average value was calculated.

[0149] The OH group concentration in the four directions of the cylinder circumference was measured, and it was found that the OH group concentration was 195-255 ppm, and the maximum difference between the four directions was 60 ppm, and the variation relative to the average value of the four directions was 26.7%, which was lower than that of Examples 1 and 2. In addition, the chlorine concentration was less than 20 ppm.

[0150] (Example 4)

[0151] A hollow porous quartz glass base material was obtained by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, a soot body was manufactured under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 200 mm / min (fixed), and a surface peripheral speed of 9 m / min (fixed), and a swing displacement α of 4 mm per swing (the irradiation diameter of the flame at this time was 28 mm, so the swing displacement was 1 / 7 of the irradiation diameter of the flame. The flame diameter was measured by image analysis of the flame during the growth of the soot body.), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4, and the measurement results of the synthetic quartz glass cylinder are shown in Table 5.

[0152] When growing from a target OD of 50 mm to a soot body OD of 400 mm, the rotation speed is reduced from 57.3 rpm to 7.2 rpm under the above conditions. The minimum rotation speed N at this time is m It is 7.2rpm, γ=0.28.

[0153] As a result, a large hollow porous silica glass base material with an outer diameter of 400 mm, a total length of 3500 mm, and a weight of 247 kg can be produced without vibration during growth of the device or cracks in the soot body.

[0154] The average density of the entire soot body and the density variation are measured. Figure 6 The density per unit length at the four points where X = 105 mm is calculated. The average density of the entire soot body is 0.57 g / cm 3 The density variation per unit length at a position 105 mm from the inner surface in four directions is 1.6% / cm relative to the average value of the four points, and a hollow porous quartz glass base material with extremely small density variation is obtained.

[0155] The obtained hollow porous quartz glass base material was dehydrated and sintered in a chlorine atmosphere to obtain a synthetic quartz glass tube with an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member and had a good appearance.

[0156] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of chlorine concentration, the difference between the maximum and minimum chlorine concentrations at four locations 50 mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0157] The chlorine concentration in the four directions of the cylinder was measured, and the result was that the chlorine concentration was 1860-1995ppm. The maximum difference between the four directions was 135ppm, and the variation relative to the average value of the four directions was a uniform variation of 6.9%. In addition, the OH group concentration (OH group) was less than 1ppm.

[0158] Furthermore, the soot body produced under the same conditions was heated to dehydrate without chlorine treatment, and then sintered and transparentized to obtain a synthetic quartz glass tube with an outer diameter of 210 mm, an inner diameter of 45 mm or less, and a length of 3.4 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member, and had a good appearance.

[0159] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. The variation of the OH group concentration was determined by measuring the difference between the maximum and minimum OH group concentrations at four locations 50 mm from the inner surface of the cylinder cross section at every 90° in the circumferential direction, and calculating the ratio to the average value of the four points.

[0160] The OH concentration in the four directions around the cylinder was measured and found to be 200-215 ppm. The difference between the four directions was as small as 15 ppm, and the variation relative to the average value in the four directions was also uniform at 7.1%. In addition, the chlorine concentration was less than 20 ppm.

[0161] (Example 5)

[0162] A hollow porous quartz glass base material was obtained by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, a soot body was produced under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 200 mm / min (fixed), and a surface peripheral speed of 13 m / min (fixed), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4, and the measurement results of the synthetic quartz glass cylinder are shown in Table 5.

[0163] When growing from a target OD of 50 mm to a soot body OD of 600 mm, the rotation speed is reduced from 82.8 rpm to 6.9 rpm under the above conditions. The minimum rotation speed N at this time is m It is 6.9rpm, γ=0.29.

[0164] As a result, a large hollow porous silica glass base material with an outer diameter of 600 mm, a total length of 2500 mm, and a weight of 402 kg can be produced without vibration during growth of the device or cracks in the soot body.

[0165] The average density of the entire soot body and the density variation are measured. Figure 6 The density per unit length at the four points where X = 200 mm is calculated. The average density of the entire soot body is 0.57 g / cm 3 The density variation per unit length at a position 200 mm away from the inner surface in four directions is 3.7% / cm relative to the average value of the four points, and a hollow porous quartz glass base material with extremely small density variation is obtained.

[0166] The obtained hollow porous quartz glass base material was dehydrated and sintered in a chlorine atmosphere to obtain a synthetic quartz glass tube with an outer diameter of 350 mm, an inner diameter of 45 mm or less, and a length of 1.9 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member and had a good appearance.

[0167] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of chlorine concentration, the difference between the maximum and minimum chlorine concentrations at four locations 100 mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0168] The chlorine concentration in the four directions of the cylinder was measured, and the results showed that the chlorine concentration was 1890-2170 ppm. The maximum difference between the four directions was as small as 280 ppm, and the variation relative to the average value of the four directions was a homogeneous variation of 14.1%. In addition, the OH group concentration (OH group) was less than 1 ppm.

[0169] Furthermore, the soot body produced under the same conditions was heated to dehydrate without chlorine treatment, and then sintered and transparentized to obtain a synthetic quartz glass tube with an outer diameter of 350 mm, an inner diameter of 45 mm or less, and a length of 1.9 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member, and had a good appearance.

[0170] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of OH group concentration, the difference between the maximum and minimum OH group concentrations at four locations 50 mm from the inner surface of the cylinder cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0171] The OH concentration in the four directions around the cylinder was measured and found to be 225-245 ppm. The difference between the four directions was as small as 25 ppm, and the variation relative to the average value of the four directions was also uniform at 10.5%. In addition, the chlorine concentration was less than 20 ppm.

[0172] (Example 6)

[0173] A hollow porous quartz glass base material was obtained by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, a soot body was produced under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 400 mm / min (fixed), and a surface peripheral speed of 9 m / min (fixed), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4, and the measurement results of the synthetic quartz glass cylinder are shown in Table 5.

[0174] When growing from a target OD of 50 mm to a soot body OD of 600 mm, the rotation speed is reduced from 57.3 rpm to 4.8 rpm under the above conditions. The minimum rotation speed N at this time is m It is 4.8rpm, γ=0.84.

[0175] As a result, a large hollow porous silica glass base material with an outer diameter of 600 mm, a total length of 2500 mm, and a weight of 402 kg can be produced without vibration during growth of the device or cracks in the soot body.

[0176] The average density of the entire soot body and the density variation are measured. Figure 6 The density per unit length at the four points where X = 200 mm is calculated. The average density of the entire soot body is 0.57 g / cm 3 The density variation per unit length at a position 200 mm from the inner surface in four directions is 8.3% / cm relative to the average value of the four points.

[0177] The obtained hollow porous quartz glass base material was dehydrated and sintered in a chlorine atmosphere to obtain a synthetic quartz glass tube with an outer diameter of 350 mm, an inner diameter of 45 mm or less, and a length of 1.9 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member and had a good appearance.

[0178] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of chlorine concentration, the difference between the maximum and minimum chlorine concentrations at four locations 100 mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0179] The chlorine concentration in the four directions around the cylinder was measured, and the chlorine concentration was 1725 to 2340 ppm. The difference in the four directions was as large as 615 ppm, and the variation relative to the average value in the four directions was 29.1%, which showed a decrease in homogeneity compared with Examples 4 and 5. In addition, the OH group concentration (OH group) was less than 1 ppm.

[0180] Furthermore, the soot body produced under the same conditions was not subjected to chlorine treatment but was dehydrated by heating, and then sintered and transparentized to obtain a synthetic quartz glass tube having an outer diameter of 350 mm, an inner diameter of 45 mm or less, and a length of 1.9 m. The obtained synthetic quartz glass tube had no appearance defective parts caused by cracks in the porous member and had a good appearance.

[0181] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of OH group concentration, the difference between the maximum and minimum OH group concentrations at four locations 50 mm from the inner surface of the cylinder cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0182] The OH group concentration in the four directions of the cylinder circumference was measured, and it was found that the OH group concentration was 200-250 ppm. The maximum difference between the four directions was 50 ppm, and the variation relative to the average value of the four directions was 21.7%, which was lower than that of Examples 4 and 5. In addition, the chlorine concentration was less than 20 ppm.

[0183] (Example 7)

[0184] A hollow porous quartz glass base material was obtained by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, a soot body was manufactured under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 200 mm / min (fixed), and a surface peripheral speed of 13 m / min (fixed), and a swing displacement α of 4 mm per swing (the irradiation diameter of the flame at this time was 28 mm, so the swing displacement was 1 / 7 of the irradiation diameter of the flame), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4, and the measurement results of the synthetic quartz glass cylinder are shown in Table 5.

[0185] When growing from a target OD of 50 mm to a soot body OD of 600 mm, the rotation speed is reduced from 82.8 rpm to 6.9 rpm under the above conditions. The minimum rotation speed N at this time is m It is 6.9rpm, γ=0.29.

[0186] As a result, a large hollow porous silica glass base material with an outer diameter of 600 mm, a total length of 2500 mm, and a weight of 402 kg can be produced without vibration during growth of the device or cracks in the soot body.

[0187] The average density of the entire soot body and the density variation are measured. Figure 6 The density per unit length at the four points where X = 200 mm is calculated. The average density of the entire soot body is 0.57 g / cm 3 The density variation per unit length at a position 200 mm from the inner surface in four directions was 1.8% / cm relative to the average value of the four points, and a hollow porous quartz glass base material with extremely small density variation was obtained.

[0188] The obtained hollow porous quartz glass base material was dehydrated and sintered in a chlorine atmosphere to obtain a synthetic quartz glass tube with an outer diameter of 350 mm, an inner diameter of 45 mm or less, and a length of 1.9 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member and had a good appearance.

[0189] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of chlorine concentration, the difference between the maximum and minimum chlorine concentrations at four locations 100 mm from the inner surface of the cylindrical cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0190] The chlorine concentration in the four directions of the cylinder was measured. The results showed that the chlorine concentration in the four directions was 1770-1935 ppm, with the maximum difference being as small as 165 ppm. The variation relative to the average value in the four directions was a uniform variation of 8.8%. In addition, the OH group concentration (OH group) was less than 1 ppm.

[0191] Furthermore, the soot body produced under the same conditions was heated to dehydrate without chlorine treatment, and then sintered and transparentized to obtain a synthetic quartz glass tube with an outer diameter of 350 mm, an inner diameter of 45 mm or less, and a length of 1.9 m. The obtained synthetic quartz glass tube did not contain any defective appearance caused by cracks in the porous member, and had a good appearance.

[0192] The chlorine concentration and OH group concentration of the obtained quartz glass cylinder were measured. Regarding the change of OH group concentration, the difference between the maximum and minimum OH group concentrations at four locations 50 mm from the inner surface of the cylinder cross section at every 90° in the circumferential direction was measured, and the ratio to the average value of the four points was calculated.

[0193] The OH concentration in the four directions around the cylinder was measured and found to be 205-225 ppm. The difference between the four directions was as small as 20 ppm, and the variation relative to the average value of the four directions was also uniform at 9.4%. In addition, the chlorine concentration was less than 20 ppm.

[0194] (Comparative Example 1)

[0195] The hollow porous quartz glass base material was manufactured by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, the soot body was manufactured under the conditions of burner interval of 100 mm, swing distance L of 100 mm, swing speed S of 140 mm / min (fixed), and surface peripheral speed of 18 m / min (fixed).

[0196] When growing from a target OD of 50 mm to a soot body OD of 400 mm, the rotation speed was slowed down from 114.6 rpm to 14.3 rpm under the above conditions. However, the vibration of the device began near the soot body OD exceeding 200 mm, and the vibration was large when the soot body OD exceeded 250 mm, so the production was stopped halfway and could not be continued to OD 400.

[0197] (Comparative Example 2)

[0198] A hollow porous quartz glass base material was produced by the same method as in Example 1 except that the production conditions were changed as shown in Table 3. That is, a soot body was produced under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 800 mm / min (fixed), and a surface peripheral speed of 9 m / min (fixed), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4.

[0199] When growing from a target OD of 50 mm to a soot body OD of 400 mm, the rotation speed is reduced from 57.3 rpm to 7.2 rpm under the above conditions. The minimum rotation speed N at this time is m The rotation speed was 7.2 rpm, and γ = 1.12. As a result, although the growth was possible without vibration of the device during growth, when the OD of the soot body reached about 300 mm, cracks entered the soot body and the production could not be continued.

[0200] (Comparative Example 3)

[0201] A hollow porous quartz glass base material was manufactured by the same method as in Example 1 except that the manufacturing conditions were changed as shown in Table 3. That is, a soot body was manufactured under the conditions of a burner interval of 100 mm, a swing distance L of 100 mm, a swing speed S of 800 mm / min (fixed), and a surface peripheral speed of 9 m / min (fixed), and a swing displacement α of 4 mm per swing (the irradiation diameter of the flame at this time was 28 mm, so the swing displacement was 1 / 7 of the irradiation diameter of the flame. The method for measuring the flame diameter was image analysis of the flame during the growth of the soot body.), and a target was extracted from the soot body to obtain a hollow porous quartz glass base material. The results of the obtained hollow porous quartz glass base material are shown in Table 4.

[0202] When growing from a target OD of 50 mm to a soot body OD of 400 mm, the rotation speed is reduced from 57.3 rpm to 7.2 rpm under the above conditions. The minimum rotation speed N at this time is m The rotation speed was 7.2 rpm, and γ = 1.12. As a result, although the growth was possible without vibration of the device during growth, when the OD of the soot body reached about 350 mm, cracks entered the soot body and the production could not be continued.

Claims

1. A large hollow porous quartz glass base material, which is a cylindrical large hollow porous quartz glass base material with an outer diameter exceeding 300 mm and a length exceeding 2 m, characterized in that: The average density of the base material is 0.55 g / cm 3 The above, and the density variation per unit length at four points equidistant from the inner surface in the radial direction in four directions of every 90° of the cylindrical cross section is less than 10% / cm relative to the average value of the four points, and does not include cracks.

2. A large hollow porous quartz glass base material, which is a cylindrical large hollow porous quartz glass base material with an outer diameter of 500 mm or more and a length of 1.0 m or more, characterized in that: The average density of the base material is 0.55 g / cm 3 The above, and the density variation per unit length at four points equidistant from the inner surface in the radial direction in four directions of every 90° of the cylindrical cross section is less than 10% / cm relative to the average value of the four points, and does not include cracks.

3. A hollow synthetic quartz glass cylinder, characterized in that: The hollow porous quartz glass base material according to claim 1 or 2 is obtained by dehydrating and vitrifying, having an outer diameter of 200 to 500 mm, a length of 0.7 m to 3.5 m, an OH group concentration of less than 5 ppm, a chlorine concentration of 500 ppm to 3000 ppm, and does not contain an appearance defect caused by cracks in the porous member.

4. The hollow synthetic quartz glass cylinder according to claim 3, characterized in that: The "difference between the maximum value and the minimum value" of the chlorine concentration at four positions every 90° in the circumferential direction which are equidistant from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass cylinder is within 15% of the average value of the four positions.

5. A hollow synthetic quartz glass cylinder, characterized in that: The hollow porous quartz glass base material according to claim 1 or 2 is obtained by pre-sintering and vitrifying, has an outer diameter of 200 to 500 mm, a length of 0.7 m to 3.5 m, an OH group concentration of 50 ppm to 500 ppm, and does not contain appearance defects caused by cracks in the porous member.

6. The hollow synthetic quartz glass cylinder according to claim 5, characterized in that: The “difference between the maximum and minimum values” of the OH group concentration at four positions every 90° in the circumferential direction which are equidistant from the inner surface of the cylindrical cross section of the hollow synthetic quartz glass cylinder is within 15% of the average value of the four positions.

Citation Information

Patent Citations

  • Production of matrix for optical fiber preform

    JP1991228845A

  • Method for manufacturing quartz glass body

    JP2001504426A

  • Method of producing optical fiber preform

    JP2002167228A

  • Method for producing glass fine particle deposited body

    JP2013043810A